2000
DOI: 10.1111/j.1471-0528.2000.tb11609.x
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression: identification of women at risk

Abstract: trial are effective in their own right. A further incentive for involvement in the trial is the concept of thèone-stop' (or`twoor`two-stop' in the case of our research clinic) menstrual disorders clinic. This type of clinic had not previously been established in our hospital and women otherwise have their menorrhagia managed routinely in a general gynaecology clinic. On completion of the trial, the dedicated menstrual disorders clinic will continue as a routine clinical service. To answer the question asked by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
102
6
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(134 citation statements)
references
References 59 publications
(59 reference statements)
14
102
6
9
Order By: Relevance
“…4,5 Berry M et al, Forman N et al have found an increased association of multipara with PPD whereas More B et al found primiparity to be associated with PPD. 4,6,7 Like in our study, Josefsson et al have concluded that no association exists between parity and PPD. 8 In present study women who had operative delivery (CS) had significant relationship with PPD.…”
Section: Discussioncontrasting
confidence: 42%
“…4,5 Berry M et al, Forman N et al have found an increased association of multipara with PPD whereas More B et al found primiparity to be associated with PPD. 4,6,7 Like in our study, Josefsson et al have concluded that no association exists between parity and PPD. 8 In present study women who had operative delivery (CS) had significant relationship with PPD.…”
Section: Discussioncontrasting
confidence: 42%
“…Social support in particular has been shown to influence the attitudes, emotions, and behaviors of new mothers [11,29]. Neilson [18] identified social isolation and psychological stress, as significant predictors of PPD. Although some of these risk factors (e.g., socioeconomic status) are not easily inferred via social media posts, proxies for several factors could be monitored.…”
Section: Risk and Presence Of Postpartum Changesmentioning
confidence: 99%
“…Many predictors of PND are associated with social adversity rather than with any biological traits 6 . Factors strongly associated with PND include a past history of psychiatric disorder (usually depression), poor marital relationship, lack of social support and recent stressful life events 7 . Social status, family income and occupational status of the mother are only weakly associated with PND 6 .…”
mentioning
confidence: 99%